A primazia do sensível sobre o inteligível em paixões pandêmicas: O que restou dos estados de alma? - SILVANA REGINA MARTINS BRIXNER (2024)
This research proposes a semiotic reading of the passions - from those that affect us to those that animate us - in the context of the COVID-19 pandemic, in the year 2020, seeking to situate states of the soul with the analysis of passional subjects' paths during the pandemic period repercussed on a global scale and felt on a human scale. We consider the passionate not only as a syntagmatic organization, but also in its tensive and sensitive configuration. As corpus, we made use of a North American website that receives reports about losses and adaptations imposed by Covid-19 called Coronavirus Lost and Found - A Pandemic Archive, seeking to identify manifestations through written production that allow the understanding of how feelings and emotions are manifested in the construction of hundreds of reports from the most diverse parts of the planet, which allowed us to study that demonstrate that people share feelings of search or distance, of finding or losing, similar in form and different in content. To do so, we resorted to Greimas and Fontanille's semiotics of the passions, their analysis being contextualized in terms of modal syntax - devices and combinations of modalities that structure the state of the narrative subjects with different tensions, directions, forces, forias. Thus, we verify how these, overmodalized by believing travel the course of a will-can-know/be or do, considering also tensive postulates in this regard.